2017
DOI: 10.1111/risa.12896
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Expected Immediate Reactions to Severe Storm Displays

Abstract: The National Weather Service has adopted warning polygons that more specifically indicate the risk area than its previous county-wide warnings. However, these polygons are not defined in terms of numerical strike probabilities (p ). To better understand people's interpretations of warning polygons, 167 participants were shown 23 hypothetical scenarios in one of three information conditions-polygon-only (Condition A), polygon + tornadic storm cell (Condition B), and polygon + tornadic storm cell + flanking nont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…This is consistent with our finding that some participants in border areas perceived their local warning level to be yellow, while others perceive it to be amber. It may also reflect a broader tendency for those on the periphery of warning areas to perceive their own level of risk to be lower than those in the center (Jon et al 2018;Lindell et al 2016). Once again, this highlights the importance of members of the public being able to identify the warning level in place for their location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our finding that some participants in border areas perceived their local warning level to be yellow, while others perceive it to be amber. It may also reflect a broader tendency for those on the periphery of warning areas to perceive their own level of risk to be lower than those in the center (Jon et al 2018;Lindell et al 2016). Once again, this highlights the importance of members of the public being able to identify the warning level in place for their location.…”
Section: Discussionmentioning
confidence: 99%
“…Second, when a location is close to the border of two warning levels on the map how is local risk level interpreted? Research on tornado warning maps suggests that people perceive areas near the warning periphery as lower risk than central areas, despite this not being the case (Jon et al 2018(Jon et al , 2019Lindell et al 2016). For U.K. weather warnings, it is thus useful to determine whether those close to the border of different warning levels (e.g., yellow and amber) perceive personal risk differently than those clearly within one warning level and whether this affects behavioral response.…”
Section: ) Warning Mapsmentioning
confidence: 99%
“…How can this be done most effectively, if there is to be a balanced response without risking panic? Jon, Huang, and Lindell (2019) in this special issue consider the case of tornados in the United States. They note that little research has been conducted into how people actually interpret and respond to the warning polygons used by the National Weather Service.…”
Section: Stage 5: Communication and Presentation Of Resultsmentioning
confidence: 99%
“…The method in which hazard information is conveyed through warnings and graphics can also affect how individuals perceive data to inform their decision to evacuate. It has been observed that the type of graphic presented to an individual can influence their protective action decisions and that different methods of information portrayal with natural hazards can alter an individual's risk perception [41][42][43][44]. For example, the study by Ash tested the response to three different tornado warning designs [41].…”
Section: Evacuation Behaviormentioning
confidence: 99%